Niche characteristics of lichen in Dabancheng mountainous area, Urumqi - Zuosen LI; Anwar TUMUR (Guangxi Zhiwu, 2023)
In order to reveal the status of habitat resource utilization and the degree of competition among lichens in Dabancheng mountainous areas. In this work, 30 plots were sampled in the field and the species cover data of the plots were investigated, and the niche characteristics and environmental factors of lichen community species were analyzed by using niche width, niche overlap index and ordination analysis in this Dabancheng mountainous area. The results were as follows: (1) The niche width of Rusavskia elegans and Circinaria contorta were the widest in Dabancheng mountainous area, indicating that they were more adaptable to different environments. The niche widths of other lichen species were narrow, indicating that the species used the environmental resources to a less extent. (2) The niche overlap value between species was generally low, with only a few species pairs having a high niche overlap value. The degree of niche differentiation between lichen species was high, indicating that the competition between species was not intense. (3) Although niche overlap was common among species with wider niche widths, niche overlap values were lower. However, some species with narrower niche widths had higher niche overlap values with other species. As a result, there was no clear linear relationship between niche overlap and niche width. (4) The distribution of lichen species varied along the altitudinal gradient, and altitude, light intensity, humidity, wind speed, and human disturbance were the dominant environmental factors for the different niche characteristics of lichen community species in the study area. In conclusion, as a result of habitat resource competition in Dabancheng mountainous area, lichen species occupied their own distinct niches, resulting in niche differentiation and relatively stable communities. The distribution of species differed significantly due to differences in habitat conditions along the altitudinal gradient. The results of this paper provides a theoretical basis for the study of lichen community assembly, which are of great significance to the conservation of lichen species diversity and habitat in the region.